Building the Character of Science Students through Innovative Learning Based on Process Skills During the Covid-19 Pandemic - Rosita Saragih; Elisabeth Sitepu; Rosma Nababan; Selamat Karo-Karo (Postgraduate, University of Mataram, 2023)
The aim of this research is to describe student character through innovative learning based on process skills in class IX of Jambi Medan Private High School during the Covid-19 pandemic. This research is qualitative research, the research subjects were 34 students in class IX of Jambi Medan Private High School. Data collection techniques were obtained through interviews and questionnaires. The research results show that the science learning process in class IX of Jambi Medan Private High School during the Covid-19 pandemic was carried out offline using a shift system by applying a discovery learning model with a process skills-based approach and combined with several learning methods of mind mapping, group discussions, questions and answers and assignments. Student participation in learning during the Covid-19 pandemic was good. Students participate actively in the learning process. Assessment of student learning outcomes reaches the Minimum Completeness Criteria (KKM).